(untitled) (Praxis Educativa, 2017)
The initial teacher training of elementary school teachers in Chile, which has its origins in “the normal schools” and the University of Chile, is currently influenced by new paradigms arising from the emergence of neoliberalism in the 80s. The impact of that model in the educational curriculum is the introduction of standards and indicators as parameters for the accreditation of teaching programs and the demands imposed by the model of competencybased training. In this scenario, one can reflect on the challenge that arises from such training, particularly on the impact of that model for the new generations of teachers, which implies the training of ideally competent professionals, moving from the training capacity based on cultural and scientific facts to the academic development of the modern professional.